Urban conservation in a comparative perspective : Dublin and Stockholm - Negussie, Elene (Trinity College (Dublin, Ireland). Department of Geography, 2003)
This thesis explores differing approaches to urban conservation in the cities of Dublin and Stockholm. It examines the impact of Central Government policies that have addressed directly or had indirect impact upon urban conservation in Dublin City since the 1950s. It further reviews the evolution of approaches to urban conservation embodied in, and implemented through local-authority urban planning policies. Also, it explores the contribution and role played by the voluntary sector in promoting and effecting urban conservation. The research broadens its scope by providing a cross- cultural comparison of contemporary conservation policies in Dublin and Stockholm. The study explores the impact of cultural and political ideas underlying varying approaches to conservation policy and its implementation. This enables sharper focus to be given to establishing the basis upon which certain urban elements become deemed worthy of conservation and the manner in which such evaluations and appraisals have tended to change over time.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin